Female hair loss. Issue 10 (October 2019) - Middleton, David W; McCourt, Collette
Hair loss in female patients is a distressing condition. Patients can present to GPs for assessment, advice and consideration of onward referral. A wide range of disorders can lead to hair loss in females. This article will outline common disorders and their clinical features, including investigation and management strategies for primary and secondary care. A sound understanding of the course and prognosis of diseases allows open discussion with patients during healthcare consultations, and is important given the distressing nature of hair loss.